Metode dan Media Pembelajaran untuk Pendidikan Inklusi bagi Penyandang Autis di Indonesia - Agung Rustandar; Dini Widinarsih (Jurnal Pendidikan Kebutuhan Khusus, 2023)
This article aims to reveal variety of learning methods and media to support persons with autism’s need to inclusive education, based on literature review. It revealed from previous studies published during 2013-2021 that there are 9 methods, 8 learning media with variety fulfillment on the cognitive, affective and psychomotor aspects of learning. Significance of this study revealed that those various learning methods and media are affordable options to various socio-economic conditions of society in Indonesia. Novelty of this study is accumulation knowledge to be applied by parties who concerns to inclusive education and fulfillment of the learning needs of persons with autistic.